Validity and reliability of the Health-Related Quality of Life Instrument with 8 Items (HINT-8) in Korean breast cancer patients - Juyoung Kim (Korea Centers for Disease Control & Prevention, 2021)
Objectives This study evaluated the validity and reliability of the Health-Related Quality of Life Instrument with 8 Items (HINT-8) in postoperative breast cancer patients in South Korea. Methods The study included 300 breast cancer patients visiting a tertiary hospital. We measured health-related quality of life (HRQoL) using the HINT-8, the 5-level EQ-5D version (EQ-5D-5L), and the Functional Assessment of Cancer Therapy-Breast (FACT-B). Discriminatory ability, known-group validity, and convergent validity were assessed. Reliability was evaluated with the Cohen kappa, weighted kappa, and intraclass correlation coefficient (ICC). Results The EQ-5D-5L indexes (p<0.001) and EQ visual analogue scale (VAS) scores (p<0.001) were significantly higher in subjects with no problems in each item of the HINT-8 than in those with problems. The FACT-B total scores were also higher in subjects without problems on the HINT-8. Older age, lower education level, and comorbidities were associated with a lower HINT-8 index. The HINT-8 index was correlated with the EQ-5D-5L index and the EQ VAS, with correlation coefficients of 0.671 (p<0.001) and 0.577 (p<0.001), respectively. The correlation coefficients between the HINT-8 and the FACT-B ranged from 0.390 to 0.714. The ICC was 0.690 (95% confidence interval, 0.580–0.780). Conclusion The HINT-8 showed appropriate validity for capturing HRQoL in postoperative breast cancer patients.